2017
DOI: 10.1111/aas.13023
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological effects of desflurane in children with Wolff‐Parkinson‐White syndrome: a randomized crossover study

Abstract: Desflurane enhances the refractoriness and may block the electrical conduction of the atrioventricular accessory pathway, and is therefore not suitable for use in children undergoing radiofrequency catheter ablation for WPW syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Moreover, propofol did not affect the refractory periods of normal and accessory pathways and did not interfere with EPS/ablation in a study with adult WPW patients [22]. Also, in children, propofol-based anaesthesia did not cause problems during EPS/RFCA [23,24]. Two randomised studies in youngsters undergoing RFCA, showed that propofol was similarly suitable with isoflurane, both leaving unaffected the SA and AV node function [25,26].…”
Section: Anaesthesia For Electrophysiologic Investigation and Ablationmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, propofol did not affect the refractory periods of normal and accessory pathways and did not interfere with EPS/ablation in a study with adult WPW patients [22]. Also, in children, propofol-based anaesthesia did not cause problems during EPS/RFCA [23,24]. Two randomised studies in youngsters undergoing RFCA, showed that propofol was similarly suitable with isoflurane, both leaving unaffected the SA and AV node function [25,26].…”
Section: Anaesthesia For Electrophysiologic Investigation and Ablationmentioning
confidence: 99%
“…Also in children, when given after propofol, sevoflurane caused only moderate prolongation of the AP antegrade effective refractory period, without interfering with the ablative procedure [33]. On the other hand, desflurane at 1 MAC prolonged the AP effective refractory period and impaired the induction of diagnostic SVTs in paediatric patients [24]. The authors considered it unsuitable for EPS/ablative procedures [24].…”
Section: Anaesthesia For Electrophysiologic Investigation and Ablationmentioning
confidence: 99%
See 2 more Smart Citations
“…Propofol is the most commonly used intravenous anaesthetic worldwide and has advantages over inhalation anaesthesia such as less postoperative nausea and emergence delirium especially in children, 1 widely used for anaesthesia to radiofrequency catheter ablation (RFCA) in paediatric patients, 2 and favoured over volatile anaesthetics 3 . Propofol is a safe intravenous anaesthetic, but can rarely cause severe atrioventricular (AV) blocks in humans 4‐9 .…”
Section: Introductionmentioning
confidence: 99%